2013
DOI: 10.4314/ajcem.v15i1.6
|View full text |Cite
|
Sign up to set email alerts
|

Microbial status of smoked fish, <i>scombia scombia</i> sold in Owerri, Imo state, Nigeria

Abstract: As one of the common sources of protein available to man, fish is highly consumed due to its lower cholesterol content and price. So it forms a rich protein source for both poor and rich. As a part of checkmating the public health risks associated with this general dependence of the population on fish, the microbiological assessment of smoked fish, Scombia, scombia sold in Owerri was embarked on with the aim of ascertaining the microbial quality, the presence and prevalence of microorganisms of public health i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 2 publications
4
6
0
Order By: Relevance
“…This is in agreement with the results of Dike-Ndudim et al (2014) who attribute the isolation of the same organisms from smoked fish sold in Owerri to feacal contamination of water sources in Owerri.…”
Section: Discussionsupporting
confidence: 82%
“…This is in agreement with the results of Dike-Ndudim et al (2014) who attribute the isolation of the same organisms from smoked fish sold in Owerri to feacal contamination of water sources in Owerri.…”
Section: Discussionsupporting
confidence: 82%
“…Microsporum canisand Trichophyton mentagrophytes which are zoophilic originated from cats, dogs and other domestic animals are among the organisms found and isolated. Similar findings were reported by Dike-Ndudim et al[23], they reported the isolation of M. canis and T. mentagrophytes among children in Isu Local Government of Imo State, Nigeria. Trichophyton rubrum and Microsporum audouinii were also isolated from the children.…”
supporting
confidence: 89%
“…This could be attributed to poor hygiene practice during handling and smoking processes. The reason could as well be an indication of partial dehydration during smoking and unhygienic display at market stalls, as earlier observed by Dike-Ndudim et al [24].…”
Section: Methods Of Preserving Bonga Fish In the Areasupporting
confidence: 60%